33 Assessing the impact of a novel community based education programme on the self management of hypertension. (October 2018) - Gibson, I; Rabbitte, M; Darrat, M; Houlihan, A; Hearn, A; Flaherty, G; Sharif, F
Abstract : Background: Hypertension is a leading modifiable risk factor for cardiovascular disease and is estimated to be responsible for at least 45% of ischaemic heart disease mortality and 51% of stroke mortality globally. Irish studies indicate a prevalence of 64% of hypertension amongst adults over 50 years with accompanying low levels of patient knowledge, and sub-optimal clinical management. Purpose: This study was designed to explore the impact of a structured hypertension educational intervention on patient knowledge, lifestyle behaviours and blood pressure (BP) control. Methods: Participants were recruited through community-based screening events; and those with hypertension were randomly assigned to control and intervention groups. At baseline, both groups received standard care which included; completing a knowledge questionnaire, BP assessment supported by lifestyle advice and referral to General Practice in accordance with ESC best practice guidelines. The intervention group received an additional educational intervention delivered by a multidisciplinary team. Educational topics included understanding and taking control of BP, the effects of exercise and diet on BP, smoking cessation, stress management, and medication updates and adherence. Both groups were followed up at 4 months. Results: 200 individuals were recruited to the study with 118 meeting the eligibility criteria and being randomised to the intervention (n=59) and control group (n=59). Significant improvements (p<0.001) were found in the intervention group compared with the control group across all 9 knowledge questions. Greater improvements were noted in the intervention group across a number of lifestyle variables. Mean exercise levels increased from 30 minutes/day to 45 minutes/day (p<0.002), mean weight reduced from 77.0 kgs to 70.6 kgs (p<0.003), and a significant number of intervention participants reduced their salt intake in comparison to control participants. Participants who received the intervention showed a greater reduction in both systolic (SBP) and diastolic (DBP) blood pressure (SBP 158.8 mmHg to 141.6 mmHg, p<0.0001 and DBP 84.7 mmHg to 77.7 mmHg, p<0.001). Conclusion: Providing tailored education to individuals with hypertension can positively impact patient knowledge, engagement and self-care management thus leading to improved BP control. Given that elevated BP is a leading risk factor for disease burden globally, it is imperative that new models of care are developed to improve hypertension management in the community.